General Review on Cognitive Behavior Play Therapy on Childrens’ Psychology Development - Nor Hamizah Ab Razak; Ku Suhaila Ku Johari; Mohd Izwan Mahmud; Nadziroh Md Zubir; Sabihah Johan (Human Resource Management Academic Research Society, 2024)
This research is on general review regarding play therapy application as a counseling intervention in helping improving of psychology development in children. Discussions in this work are focused on Cognitive-Behavioral Play Therapy (CBPT) which is emphasizes on childrens’ development. CBPT is a structural and directive efforts that focuses on children’s experience. CBPT developments are results of adaptation and evolution of Cognitive Theory which initially has been developed for adults, and adapted accordingly to children’s needs. A lot of challenging issues has been giving negative impact to children’s psychological and mental health. Thus, this group deserves a suitable treatment that matches their development. CBPT has been identified as a suitable intervention in treating psychological issues involving children.